Do religiosity, halal knowledge, and halal certification affect Muslim students' intention to purchase halal packaged food? - Arya Bagus Wirakurnia; Ponchanok Nuanmark; Heri Sudarsono; Arga Ramadhana (Asian Journal of Islamic Management (AJIM), 2021)
Purpose: This study aims to analyze the factors that influence the intention of Muslim students in purchasing halal packaged food.Methodology: This study uses the variables of religiosity, halal knowledge, halal certification, brand, attitude, subjective norm, and perceived behavior control. The sample of this research is 239 respondents who live in West Java, Central Java, and East Java. The partial least squares structural equation model (PLS-SEM) method was used to process the research data.Findings: Halal label variables, religiosity, attitudes, subjective norms, and perceived control have a positive effect on Muslim students' intention in purchasing halal packaged food. While the variables of halal knowledge and brand image do not affect the intention in purchasing halal packaged food.Originality: Halal packaged food companies need to develop promotions of halal packaged foods that highlight Islamic nuances, including more elegant and modern Islamic symbols. Besides, the promotion is directed at efforts to reinforce the image that halal packaged food is not only individual food but also family food and Muslim student groups/organizations.